Comparison Study Between Lecture, Discussion and Collaboration Methods in Learning of the Concept of Basic Electric Circuits - Ponto, Hantje (International Journal of Psychosocial Rehabilitation, 2020)
Electricity contributes to technological development so that there is an industrial revolution4.0 in the 21st century era. Basic electric circuits (BEC) is a subject matter that must be mastered by students who pursue Electrical engineering technical competence in the Vocational Technical School (VTS). The teaching method plays an important role in the learning activities of BEC in the classroom. The use of appropriate teaching methods can help students understand the concepts of BEC subject matter. In Indonesia, there are still many teachers using the lecture method in learning activities so students often have difficulty learning the BEC concept. This study aims to conduct a study to compare lecture, discussion and collaboration methods in BEC learning activities. Participants in this study consisted of 79 students and 3 teachers. The research method is an experiment to compare the effectiveness of lecture, discussion, and collaboration methods. Data analysis uses Covariance Analysis (Ancova) to compare teaching methods and N-Gain Score testing to study the effectiveness of teaching methods in learning BEC concept.